(untitled) (Pulse, 2023)
Nephrotic Syndrome (NS) is a common childhood illness. It is a disease of relapse and remission with major concern to manage the cases with relapse. Helminthiasis also a common problem in our subcontinent. So, it is very important to find out any relation with helminthiasis and relapse in children. In our study, 88 patients, clinically diagnosed as minimal change nephrotic syndrome, were studied to find out any relationship with helminthiasis and frequent relapse. 36 patients (40.9%) had no helminthic infection, 34 patients (38.6%) had helminthiasis and 18 patients (20.5%) had atopic disorders. 62 patients were successfully followed up for 6 months. Relapses occurred 47.8% (11/23) patients in non-helminthiasis group. 88.5% (23/26) in helminthiasis group and 84.6% (11/13) in atopic group, patients who completed follow up. Thirteen percent (3) patients in non-helminthiasis group, 50% (13) in helminthiasis group and 38.5% (5) in atopic group were found to be frequent relapser. The differences were statistically significant. Pulse Volume 12-14 2020-2022 p.10-12